Glucagon Test Is a Useful Predictor of Withdrawal From Insulin Therapy in Subjects With Type 2 Diabetes Mellitus - Iwamoto, Yuichiro; Kimura, Tomohiko; Tatsumi, Fuminori; Sugisaki, Toshitomo; Kubo, Masato; Nakao, Erina; Dan, Kazunori; Wamata, Ryo; Iwamoto, Hideyuki; Takahashi, Kaio; Sanada, Junpei; Fushimi, Yoshiro; et al. (Frontiers in Endocrinology, 2022)
Aim. ₋ There are many tests for evaluating endogenous insulin secretory capacity. However, there are only a limited number of studies that have examined in detail in clinical practice which method most accurately reflects the ability to secrete endogenous insulin especially in hyperglycemic state. The purpose of this study was to find the endogenous insulin secretory capacity and a possible predictor of insulin withdrawal in subjects with type 2 diabetes requiring hospitalization due to hyperglycemia. Methods. ₋ We examined various markers for beta-cell function and searched for a useful predictor of withdrawal from insulin therapy in subjects with type 2 diabetes mellitus who were hospitalized in our institution due to hyperglycemia. Results. ₋ In the endogenous insulin secretory test during hospitalization, CPR, CPR index, and ΔCPR after glucagon loading were all significantly higher in the insulin withdrawal group. On the other hand, there were no difference in fasting CPR index, HOMA-β, SUIT, and 24-hour urinary CPR excretion between the two groups. In the glucagon test of the insulin withdrawal group, the cutoff value of ΔCPR was 1.0 ng/mL, the withdrawal rate of ΔCPR of 1.0 ng/mL or more was 69.2%, and the withdrawal rate of less than 1.0 ng/mL was 25.0%. Conclusion. ₋ It is likely that glucagon test is the most powerful tool for predicting the possibility of insulin withdrawal as well as for evaluating endogenous insulin secretory capacity in subjects with type 2 diabetes requiring hospitalization due to hyperglycemia.